2015
DOI: 10.1210/er.2015-1010
|View full text |Cite
|
Sign up to set email alerts
|

EDC-2: The Endocrine Society's Second Scientific Statement on Endocrine-Disrupting Chemicals

Abstract: The Endocrine Society's first Scientific Statement in 2009 provided a wake-up call to the scientific community about how environmental endocrine-disrupting chemicals (EDCs) affect health and disease. Five years later, a substantially larger body of literature has solidified our understanding of plausible mechanisms underlying EDC actions and how exposures in animals and humans-especially during development-may lay the foundations for disease later in life. At this point in history, we have much stronger knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
1,287
1
44

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,710 publications
(1,433 citation statements)
references
References 1,282 publications
4
1,287
1
44
Order By: Relevance
“…The second reason is the strong translational evidence already accumulated for BPA exposure as a risk factor for obesity and diabetes [2,13,19]. in this channel type in coronary smooth cells [27] and in transfected cells [28], revealing a direct channel activation by BPA via α and β1 subunits, similar to that of estradiol [18,29].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The second reason is the strong translational evidence already accumulated for BPA exposure as a risk factor for obesity and diabetes [2,13,19]. in this channel type in coronary smooth cells [27] and in transfected cells [28], revealing a direct channel activation by BPA via α and β1 subunits, similar to that of estradiol [18,29].…”
Section: Introductionmentioning
confidence: 94%
“…This action of BPA could account for the effects on reproductive function observed in epidemiological studies [2]. However, in human embryonic kidney 293 (HEK) cells expressing T-type Ca 2+ channels, acute application of BPA at different doses (0.1 nM-100 µM) inhibited the Ca 2+ current through this channel.…”
Section: Bpa Actions Onmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent comprehensive analysis revealed that sperm counts continually and significantly declined over a 38‐year period in men from Western countries 42. Numerous reports have provided evidence that a decline in sperm count links to chronic exposure to environmental endocrine disrupting chemicals (EDCs) 43, 44. Dioxins are a group of highly persistent and omnipresent EDCs 45.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that nearly 40% of the world's population still has inadequate nutritional iodine intake renders these individuals and risk groups even more vulnerable toward the adverse effects of TDCs, some of which might act as cogoitrogenic compounds interfering with the feedback regulation of the hypothalamus-pituitary-thyroid axis. In addition, interactions between the complex effects of TDC exposure and thyroid autoimmunity should be explored by taking into consideration various factors such as major sex differences in thyroid hormone-related diseases, the age of exposure, latency from exposure, synergistic effect of different EDC mixtures, nontraditional dose-response dynamics, and transgenerational effects (1).…”
mentioning
confidence: 99%